Optimizing exercise for breast cancer survivors: a randomized controlled trial of daily individualization of high-intensity online concurrent training guided by autonomic modulation - Ana Myriam Lavín-Pérez; Daniel Collado-Mateo; Inés Nieto; Xián Mayo; Carmen Hinojo González; Ana de Juan Ferré; Gary Liguori; Alfonso Jiménez (BMC Sports Science, Medicine and Rehabilitation, 2026)
Abstract Background Breast cancer and its treatments cause physical and physiological side effects that exercise can mitigate. However, there is little evidence on the effects and feasibility of high-intensity remote supervised training. In addition, there is no evidence of the effect of individualizing intensity prescription based on autonomic control in this population. Thus, this study aimed to compare the effects of two concurrent online exercise programs, pre-planned intensity prescription (PPI) and intensity prescription guided by autonomic control (HRV) on cardiorespiratory fitness (VO 2peak ), parasympathetic autonomic control, and maximum strength. Secondly, it examined programs’ compliance. Methods This 16-week randomized controlled trial involved 54 breast cancer survivors, divided into three equal groups: PPI, HRV, and a control group. PPI and HRV participants trained remotely three times per week under real-time supervision. Both training designs included progressively increased aerobic interval and strength exercises with intensity in the HRV group based on the daily root mean square of successive differences between normal heartbeats (rMSSD). Other measurements included cardiorespiratory fitness (VO 2peak ), lower and upper body 1RM maximum strength, and training load. Results The intervention showed significant differences between groups in exercise dose ( p < 0.001) and within-group intensity progression ( p < 0.001). The effects showed significant interactions in VO 2peak (32.94% vs. 10.92%, p < 0.001), LnrMSSD (9.56% vs. 4.49%, p < 0.001), and lower (65.43% vs. 30.77%, p < 0.001) and upper body 1RM strength (83.28% vs. 40.31%, p < 0.001) with greater % of improvement in the HRV group than in the PPI. Within the HRV group, significant interactions were found in VO 2peak ( p = 0.047) and 1RM squat ( p = 0.044), showing greater effects when participants completed more sessions with the intensity adjusted by HRV. Conclusion Remotely supervised exercise is feasible and effective for improving VO 2peak , autonomic control, and maximal strength in breast cancer survivors. However, daily HRV-guided high-intensity training may produce greater gains than pre-planned intensity. Additionally, women with more sessions adjusted through autonomic modulation showed greater improvements in VO 2peak and lower body strength. Trial registration The study was registered on 24/08/2021 in ClinicalTrials.gov ID NCT05040867 (https//clinicaltrials.gov/study/NCT05040867?tab=table).